Here's a little poem : a very first book of poetry - Yolen, Jane.; Peters, Andrew (Andrew Fusek); Dunbar, Polly (Cambridge, Mass. : Candlewick Press, 2007)
A collection of poems for children with the various themes of self, family, going outside, and when it is time for bed.
Includes indexes.
2.5
K-3
Keywords: Children's poetry, American; Children's poetry, English; Poetry; Poetry